A system biology perspective on environment–host–microbe interactions. (16th April 2018) - Chen, Lianmin; Garmaeva, Sanzhima; Zhernakova, Alexandra; Fu, Jingyuan; Wijmenga, Cisca
Abstract: A vast, complex and dynamic consortium of microorganisms known as the gut microbiome colonizes the human gut. Over the past few decades, we have developed an increased awareness of its important role in human health. In this review we discuss the role of the gut microbiome in complex diseases and the possible causal scenarios behind its interactions with the host genome and environmental factors. We then propose a new analysis framework that combines a systems biology approach, cross-kingdom integration of multiple levels of omics data, and innovative in vitro models to yield an integrated picture of human host–microbe interactions. This new framework will lay the foundation for the development of the next phase in personalized medicine.